Bibliometric Analysis of Gene Research on Aging - Putri, Rachmagreta Perdana; Annisa, Annisa; Tejosukmono, Ario; Yuniasih, Dewi (Universitas Ahmad Dahlan, 2024)
Aging is associated with various factors identified in the hallmark of aging. Numerous studies have been conducted to identify genes involved in the aging process, allowing for a comprehensive understanding of this phenomenon. This study aims to provide an overview of research on genes associated with the aging process. Data for this study was obtained and analyzed from the SCOPUS database covering the period from 2014 to 2024, with a focus on medicine, neuroscience, and nursing. The keywords used for the search were